BLOG TO SHARE AND GROW: A NEW TREND IN PRE-SERVICE TEACHER EDUCATION - Salli, Aysegul; Osam, Ulker Vanci (Iated-Int Assoc Technology Education & Development, 2013)
It is well known that the use of blogs in education has led to changes in delivery methods of instruction in higher education. Through the integration of blogs in pre-service teacher education, interaction and sharing among the users are aimed to contribute to their professional growth. The present study looked into whether sharing lesson plans and formal teaching experiences through short video clips encouraged interaction among a group of pre-service English teachers. The study also investigated the quality of feedback. Finally, it attempted to discover the participants' perceptions of blogging and communication through blogs. The study made use of qualitative methodology to examine the teaching practice video reflections of pre-service teachers that they shared on their blogs and the feedback from their peers to realize the type of interaction and quality of feedback. Also, the interview protocols were qualitatively analysed to gain insight in pre-service teachers' perceptions of their blog activities. The analysis of data shows that the majority of participants are positive about sharing their lesson plans and teaching practice experiences, and providing feedback to peers through blogs. However, it seems that certain other issues like readiness to use technological tools and attitudes towards the use of different online mediums need to be dealt with to make blogs a frequently used medium.
6th International Conference on Education, Research and Innovation (ICERI) -- NOV 18-20, 2013 -- Seville, SPAIN
Keywords: web 2.0; blogs; pre-service teacher education; feedback; critical reflection